2019
DOI: 10.1155/2019/8361810
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydration and Optimal Strength Combinations of Cement-Limestone-Metakaolin Ternary Composite

Abstract: Metakaolin (MK) is an aluminosilicate pozzolan material and can contribute to property development of concrete due to the pozzolanic reaction. Limestone (LS) powder presents the dilution effect, nucleation effect, and chemical effect on hydration of cement. When metakaolin and limestone are used together, due to the additional chemical reaction between the aluminum phase in MK and limestone, the synergetic benefit can be achieved. This study presents a hydration model for cement-limestone-metakaolin ternary bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Third, in future research, the following items should be studied: (1) the cost analysis of reinforced concrete structures, which considers material cost, labor cost, and indirect cost [18]; (2) the service life analysis in the operation stage, such as cracks and shrinkage, corrosion of steel rebar, and freezing and thawing [17]; (3) sustainable design method with various indicators, such as concrete performance, durability, and total cost. Moreover, the global optimal design of reinforced concrete structures with multiple aims should be performed [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, in future research, the following items should be studied: (1) the cost analysis of reinforced concrete structures, which considers material cost, labor cost, and indirect cost [18]; (2) the service life analysis in the operation stage, such as cracks and shrinkage, corrosion of steel rebar, and freezing and thawing [17]; (3) sustainable design method with various indicators, such as concrete performance, durability, and total cost. Moreover, the global optimal design of reinforced concrete structures with multiple aims should be performed [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies [21][22][23], a composite hydration model was presented for metakaolin composite concrete. Cement hydration and metakaolin reaction were simulated separately.…”
Section: A Hydration-based Strength Model Of Composite Concretementioning
confidence: 99%
See 1 more Smart Citation
“…Pozzolan is a material rich in aluminum and silicon [5], which in its finely divided form and in the presence of water, chemically reacts with calcium hydroxide. This reaction gives rise to hydrated calcium silicate and other byproducts [4,6]. Although pozzolan does not bind materials as effectively as cement, the water it contains causes it to form binding substances through certain reactions [7].…”
Section: Introductionmentioning
confidence: 99%
“…e reason for the widespread use of metakaolin is that it has economic and technological advantages over cement and concrete, which reduces the hydration heat and thus the cost of production per cement unit [11,12]. Moreover, it has been reported that it has higher pozzolanic characteristics and reduces alkali-aggregate reactions [13][14][15][16][17]. However, due to its large particles and high agglomeration, metakaolin reduces the workability and mechanical properties of cement slurry and concrete, which causes the strength of the concrete mixed with metakaolin to be lower than that of the plain concrete [14].…”
Section: Introductionmentioning
confidence: 99%